Establishment and characterization of a novel lung cell line derived from the common bottlenose dolphin - Tashiro, Kaede; Hikobe, Kyosuke; Segawa, Takao; Suzuki, Miwa; Maeda, Ken; Itou, Takuya (In vitro cellular & developmental biology. Animal, 2024)
Cetaceans are specialized marine mammals with a unique respiratory system adapted for diving behavior. Furthermore, respiratory diseases are commonly observed in these mammals. Nevertheless, much of their respiratory physiology remains unknown due to the limited supply and poor quality of their biological samples for research. In this study, we established a novel lung cell line, dLu, derived from the common bottlenose dolphin ( Tursiops truncatus ), which can prove useful in cetacean research, including for understanding the pathogenesis of respiratory diseases in cetaceans. The cells were cultured in a simple medium consisting of Dulbecco’s modified Eagle’s medium supplemented with 10% fetal bovine serum. The morphology of the cells was fibroblast-like. dLu was produced by transfecting the simian virus 40 large T antigen into primary cultured cells. Although dLu exhibited approximately 80 cell divisions, it was unable to achieve complete immortalization, as the cells stopped proliferating beyond this number. dLu cells expressed toll-like receptor 3 but not toll-like receptor 4. Immunostimulation with poly(I:C) altered the gene expressions of interferon beta 1 and tumor necrosis factor alpha in dLu cells. In summary, dLu established in this study is a novel cetacean cell resource that can be easily cultured and is a useful in vitro tool in cetacean research, particularly for studying host immune responses in the lungs.